Lower Silesia from Nazi Germany to communist Poland : 1942 - 49 - Siebel-Achenbach, Sebastian (St Antony's/Macmillan series, 1994)
Lower Silesia was one of the regions Germany lost to Poland following the Second World War. During the space of a few years, the entire territory was transformed, reversing the tradition of centuries. The eviction and suffering of the indigenous Germans is contrasted with the similar hardships the Polish resettlers were forced to undergo. Striking is the similarity of manipulation of both Silesian groups by their political masters. That Lower Silesia was ceded at all reveals much about wartime and postwar Allied negotiations which culminated in the Cold War.